Local direct democracy in Europe - Schiller, Theo (VS Verlag für Sozialwissenschaften, 2011)
Modern direct democracy has recently become an important element of political life in many countries. These developments can be observed at the national, regional, and local level of political systems. Participation and democracy in local political affairs play a major role in stabilising and developing democratic systems. This volume presents, for the first time, a broad basis of information on the wide variety of local institutions and practice of direct democracy in 19 countries. Country specialists analyse: the role of direct democracy in the institutional; context and culture of national political systems; political processes of introduction and development of initiatives and referendums; regulations of procedures of municipal direct democracy; practice of local direct democracy; the contribution of local direct democracy to democratic development in general. - Publisher's description.